Choice of music for festivals in Africa - Hyslop, Graham H. (International Library of African Music, 1955)
One of the most significant developments in the sphere of music in Africa today is the increasing popularity of Music Festivals. At most of these both African and European music is sung. In Kenya three major Festivals are held each year, one in the area of Lake Victoria, another in Nairobi, the capital of the Colony, and the third at the coast. In recent years considerable attention has been paid to the choice and treatment of African songs for performance at a Festival and the selection of the best music from the West.
Keywords: Ethnomusicology; Music festivals; Africa; Songs; Festivals; History; Criticism; African Music